2017
DOI: 10.1093/mnras/stx1138
|View full text |Cite
|
Sign up to set email alerts
|

The hELENa project – I. Stellar populations of early-type galaxies linked with local environment and galaxy mass

Abstract: We present the first in a series of papers in The role of Environment in shaping Low-mass Early-type Nearby galaxies (hELENa) project. In this paper we combine our sample of 20 low-mass early types (dEs) with 258 massive early types (ETGs) from the ATLAS 3D survey -all observed with the SAURON integral field unit (IFU) -to investigate early-type galaxies' stellar population scaling relations and the dependence of the population properties on local environment, extended to the low-σ regime of dEs. The ages in o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
71
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 87 publications
14
71
0
Order By: Relevance
“…Since galaxies with low metallicities are mainly less massive galaxies, this results in the MZR lying above that shown by Gallazzi et al (2005). The MZR with higher metallicities at the lower-mass end found here is consistent with the MZRs found in stacks of local spectra in Choi et al (2014) and in individual local early-type galaxies via integral field spectroscopy by Sybilska et al (2017). The metallicities measured by Sybilska et al (2017) were measured via spectroscopic indices using the SSP models from Vazdekis et al (2015), which is also based on the MILES library.…”
Section: Mass-metallicity Relation Of Local Galaxiessupporting
confidence: 90%
See 1 more Smart Citation
“…Since galaxies with low metallicities are mainly less massive galaxies, this results in the MZR lying above that shown by Gallazzi et al (2005). The MZR with higher metallicities at the lower-mass end found here is consistent with the MZRs found in stacks of local spectra in Choi et al (2014) and in individual local early-type galaxies via integral field spectroscopy by Sybilska et al (2017). The metallicities measured by Sybilska et al (2017) were measured via spectroscopic indices using the SSP models from Vazdekis et al (2015), which is also based on the MILES library.…”
Section: Mass-metallicity Relation Of Local Galaxiessupporting
confidence: 90%
“…The metallicities measured by Sybilska et al (2017) were measured via spectroscopic indices using the SSP models from Vazdekis et al (2015), which is also based on the MILES library. Because the measurements in Choi et al (2014), Sybilska et al (2017), and this work utilize the same stellar library, it is very likely that the choice of stellar library used caused the systematic differences in the metallicity measurements from those of Gallazzi et al (2005).…”
Section: Mass-metallicity Relation Of Local Galaxiesmentioning
confidence: 99%
“…The UDGs analysed in this work seem to display large values of [Mg/Fe] (∼ 0.4 on average). If we compare them with typical [Mg/Fe] values for dwarf systems we see that they are more similar to the values recovered in the outskirts of dwarfs (Sybilska et al 2018) or those of quenched dwarfs (Sybilska et al 2017). In addition, also the mass-metallicity relation (see Fig.…”
Section: Discussionsupporting
confidence: 67%
“…The main differences are found at the youngest ages, where we find clear signs of a quenching in the star formation that they do not detect. However, we should bear in mind that less massive galaxies (as our sample) are more susceptible to external influences than more massive systems (Sybilska et al 2017). Since the CALIFA galaxies are mainly located in low density environments (Sánchez et al 2016) and the UDGs analysed in this work lie in the Coma cluster, we may relate the existence of this quenching to either environmental effects, or the internal properties of the UDGs under analysis.…”
Section: Discussionmentioning
confidence: 98%
“…A larger (initial) satellite mass could help to explain these chemical abundances, together with the dense environment where these satellites could have lived. Sybilska et al (2017) showed as dwarfs and ellipticals in clusters tend to display higher [Mg/Fe] abundances than galaxies with similar stellar masses in the field (see also Bernardi et al 2006).…”
Section: Thick Disksmentioning
confidence: 96%